Leadership Style, Work Motivation, Work Stress, and Employee Performance: a Case Study of a Hospital - Adi Lukman Hakim; Erna Nur Faizah; Ninik Mas'adah; Fajar Rizki Widiatmoko (Universitas Gadjah Mada, 2023)
Introduction/Main Objectives: Employees are tools for achieving corporate objectives. Employees must be able to view, monitor, and comprehend the condition given the importance of leadership in the workplace. The management of human resources in medical industry is expected to enhance their job to achieve the goals, but the reality revealed their attempts fall far of what is requested for sustaining it. Background Problems: Using scientific means, the researchers attempted to answer the following research questions, namely: 1) Does leadership style have a significant impact on employee performance at the hospital industry? 2) Does work motivation have a significant impact on employee performance at the hospital industry? 3) Does job stress have a significant effect on employee performance at the hospital industry? Novelty: This research was conducted in contextual (implementation of leadership style, work motivation and work stress hospital industry). In addition, the results contribute to demonstrate how closely related the two lines of inquiry are. Research Methods: The survey consists of questionnaires, interviews, and observations of the target sample. Data were analyzed using descriptive analysis and multiple regression analysis. Finding/Results: Employee success is significantly impacted by a leader's approach in medical industry. Employee success benefits positively from work drive, and job stress has a substantial effect on employee success. Overall, at same time a leadership styles, motivation and occupational stress has a favorable and impact important influence work in a hospital of hospital industry. Conclusion: Whatever leadership style a leader chooses, they must be mindful of the behavior of their work and relationships. There are several limitations to this latest study. Future researchers may therefore apply different leadership styles to different situations.